An overview of investigational new drugs for treating ankylosing spondylitis. (2nd January 2016) - Wendling, Daniel
Abstract : Introduction : Ankylosing spondylitis (AS) is a chronic inflammatory rheumatic condition. Pharmacological treatment relies on nonsteroidal anti-inflammatory drugs, disease-modifying anti-rheumatic drugs (in case of peripheral involvement) and anti-TNF agents in case of inadequate response. To date, there are no alternate options, and about 30% of the patients do not adequately respond to anti-TNF therapy. Areas covered : This overview is based on recent publications and programmed studies. The author provides the reader with an overview of AS, its current management and provide details of novel insights into the disorder. From there, the authors highlight novel treatments under investigation before providing their expert opinion on the field. Expert opinion : The first results with biodrugs targeting the IL-23/Th17 pathway are encouraging, and secukinumab will likely be available in the forthcoming years to treat AS. Other targets may be evaluated in this axis. The author believes that additional head-to-head studies are needed find the place of these new drugs in AS treatment strategies. Further studies are also needed to better evaluate their long-term outcome and safety.